Trade‐offs and synergies of soil carbon sequestration: Addressing knowledge gaps related to soil management strategies - Maenhout, Peter; Di Bene, Claudia; Cayuela, Maria Luz; Diaz‐Pines, Eugenio; Govednik, Anton; Keuper, Frida; Mavsar, Sara; Mihelic, Rok; O'Toole, Adam; Schwarzmann, Ana; Suhadolc, Marjetka; Syp, Alina; et al. (Wiley-Blackwell, 2024)
Soil organic carbon (SOC) sequestration in agricultural soils is an important tool for climate change mitigation within the EU soil strategy for 2030 and can be achieved via the adoption of soil management strategies (SMS). These strategies may induce synergistic effects by simultaneously reducing greenhouse gas (GHG) emissions and/or nitrogen (N) leaching. In contrast, other SMS may stimulate emissions of GHG such as nitrous oxide (N2O) or methane (CH4), offsetting the climate change mitigation gained via SOC sequestration. Despite the importance of understanding trade-offs and synergies for selecting sustainable SMS for European agriculture, knowledge on these effects remains limited. This review synthesizes existing knowledge, identifies knowledge gaps and provides research recommendations on trade-offs and synergies between SOC sequestration or SOC accrual, non-CO2 GHG emissions and N leaching related to selected SMS. We investigated 87 peer-reviewed articles that address SMS and categorized them under tillage management, cropping systems, water management and fertilization and organic matter (OM) inputs. SMS, such as conservation tillage, adapted crop rotations, adapted water management, OM inputs by cover crops (CC), organic amendments (OA) and biochar, contribute to increase SOC stocks and reduce N leaching. Adoption of leguminous CC or specific cropping systems and adapted water management tend to create trade-offs by stimulating N2O emissions, while specific cropping systems or application of biochar can mitigate N2O emissions. The effect of crop residues on N2O emissions depends strongly on their C/N ratio. Organic agriculture and agroforestry clearly mitigate CH4 emissions but the impact of other SMS requires additional study. More experimental research is needed to study the impact of both the pedoclimatic conditions and the long-term dynamics of trade-offs and synergies. Researchers should simultaneously assess the impact of (multiple) agricultural SMS on SOC stocks, GHG emissions and N leaching. This review provides guidance to policymakers as well as a framework to design field experiments and model simulations, which can address knowledge gaps and non-intentional effects of applying agricultural SMS meant to increase SOC sequestration.
Keywords: CH4; climate change mitigation; conservation agriculture; cropping systems; EJPSOIL; N2O; nitrogen leaching; organic matter inputs; tillage; water management